Impacts of Human Activities on the Composition and Abundance of Sulfate-Reducing and Sulfur-Oxidizing Microorganisms in Polluted River Sediments - Wang, Rui; Xu, Shengjun; Jiang, Cancan; Zhang, Yang; Bai, Na; Zhuang, Guoqiang; Bai, Zhihui; Zhuang, Xuliang (Frontiers in Microbiology, 2019)
Water system degradation has a severe impact on daily life, especially in developing countries. However, microbial changes associated with this degradation, especially changes in microbes related to sulfur (S) cycling, are poorly understood. In this study, the abundance, structure, and diversity of sulfate-reducing microorganisms (SRM) and sulfur-oxidizing microorganisms (SOM) in the sediments from the Ziya River Basin, which is polluted by various human interventions (urban and agricultural activities), were investigated. Quantitative real-time PCR showed that the S cycling-related (SCR) genes (dsrB and soxB) were significantly elevated, reaching 2.60 × 107 and 1.81 × 108 copies per gram of dry sediment, respectively, in the region polluted by human urban activities (RU), and the ratio of dsrB to soxB abundance was significantly elevated in the region polluted by human agricultural activities (RA) compared with those in the protected wildlife reserve (RP), indicating that the mechanisms underlying water system degradation differ between RU and RA. Based on a 16S rRNA gene analysis, human interventions had substantial effects on microbial communities, particularly for microbes involved in S cycling. Some SCR genera (i.e., Desulfatiglans and Geothermobacter) were enriched in the sediments from both RA and RU, while others (i.e., Desulfofustis and Desulfonatronobacter) were only enriched in the sediments from RA. A redundancy analysis indicated that NH4+-N and total organic carbon significantly influenced the abundance of SRM and SOM, and sulfate significantly influenced only the abundance of SRM. A network analysis showed high correlation between SCR microorganisms and other microbial groups for both RU and RA, including those involved in carbon and metal cycling. These findings clarify the mechanisms underlying water quality degradation and provide a basis for monitoring and control.